Evaluating the effects of a multicomponent support service for people recently diagnosed with dementia and their carers: A qualitative study - Jonathan Ling; Karen McCabe; Ann Crosland; Laura Kane; Judith Eberhardt (Wiley, 2023)
Abstract Introduction Although prior research has provided an understanding of the needs of people living with dementia (PLWD) and their carers, less is known about how tailored multicomponent interventions impact their lives. This study explored the effect of providing ongoing support to people who had been recently diagnosed with dementia and to their carers. Methods We conducted interviews with a convenience sample of key stakeholders: 11 interviews with people who had dementia and their familial carers (n = 14) and six interviews with staff and other practitioners involved with the service (n = 13). Inductive thematic analysis was performed on the data. Results Four themes were developed: the service as a source of respite, peer support, activities as facilitators of emotional wellbeing, and social support. The service was well‐respected, credible, and trusted and was highly valued by practitioners, clients, and carers. It had a clear role in supporting PLWD and their carers. Peer support provided through the service contributed to greatly reducing self‐reported carer burden. Conclusion Recommendations arising from this study include offering holistic services to PLWD and their carers, developing activities for men, raising awareness of services among practitioners working with PLWD, and improving partnerships between services and agencies working with older people. Patient or Public Contribution Service users were consulted on the themes generated from the data and were asked to provide feedback to help guide the interpretation of the data and ensure this reflected their views and experiences.